Segmentation of Magnetic Resonance Brain Images Using Watershed Algorithm - Abdurrahim, Salem Hamed (2004)

(untitled)
An important area of current research is obtaining more information about brain structure and function. Brain tissue is particularly complex structure and its segmentation is an important step for studies intemporal change, detection of morphology as well as visualization in surgical planning, volume estimation of objects of interest, and more could benefit enormously from segmentation. Magnetic resonance imaging (MRI) is a noninvasive method for producing tomographic images of the human brain. Its Segmentation is problematic due to radio frequency inhomogeneity, caused by inaccuracies in the magnetic resonance scanner and by movement of the patient which produce intensity variation over the image, and that makes every segmentation method fail. The aim of this work is the development of a segmentation technique for efficient and accurate segmentation of MR brain images. The proposed